Kisch and Pruszyński: on Advantages and Limits of a Comparative Approach in Research on Reportage Literature - Bednarczuk, Monika (Porównania, 2021)
Reportage literature gained a growing popularity in the interwar Europe. Some reporters, such as the German journalist Egon Erwin Kisch, had a significant impact on the development of the genre of literary reportage and enjoyed a status of an international celebrity. Some others, although talented and competent, remained locally known figures, and the Polish reporter and writer Ksawery Pruszyński belongs to this second group. This paper addresses the sometimes striking similarities and differences between their biographies and texts. Kisch and Pruszyński never met, however, there are a number of reasons that back up such a comparative analysis. The paper discusses their evolving attitude towards Soviet Russia and highlights common places in their reportages, particularly Nazi Germany or the Spanish Civil War. It also focuses on a number of formal characteristics of their reportage style.